Research of hydrodynamics process in the vacuum apparatus when crystallization massecuite with the purpose of their intensification - Babko, Evhen; Veresotskiy, Yuriy; Seidykh, Olga (My University, 2013)
Computer simulation of motion of the massecuite in vacuum-tube device with additional steam injection allowed us to obtain quantitative and qualitative data on the process of heat transfer. On the basis of studies of the process of heat transfer and hydrodynamics in a vacuum apparatus proposed upgrading unit batch. It is equipped with a device for amplification of hydrodynamic circulation in order to intensify the process.Комп'ютерне моделювання руху утфелю в трубці вакуум-апарата при додатковому вдування пара дозволило отримати якісні та кількісні дані про процес теплообміну. На підставі проведених досліджень процесу теплообміну і гідродинаміки в вакуум-апаратах запропонована модернізація апарату періодичної дії. Він оснащений пристроєм для гідродинамічного посилення циркуляції з метою інтенсифікації процесу.
Keywords: steam; intensity; massecuite; пар; утфель; інтенсивність; пар; интенсивность; кафедра технологічного обладнання та комп’ютерних технологій проектування; кафедра інформаційних технологій, штучного інтелекту і кібербезпеки